2015
DOI: 10.3390/plants4020334
|View full text |Cite
|
Sign up to set email alerts
|

Root Traits and Phenotyping Strategies for Plant Improvement

Abstract: Roots are crucial for nutrient and water acquisition and can be targeted to enhance plant productivity under a broad range of growing conditions. A current challenge for plant breeding is the limited ability to phenotype and select for desirable root characteristics due to their underground location. Plant breeding efforts aimed at modifying root traits can result in novel, more stress-tolerant crops and increased yield by enhancing the capacity of the plant for soil exploration and, thus, water and nutrient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
225
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(239 citation statements)
references
References 119 publications
(113 reference statements)
1
225
0
2
Order By: Relevance
“…The spatial distribution of all root parts in a particular growth environment is referred to as root system architecture and defines the available zone of water and nutrients. This plays an important role in abiotic stress tolerance, crop performance and yield [29]. Root architecture is dynamic and affected by the external environment that impacts the way in which a plant detects and responds to its surroundings [30,31].…”
Section: Controlling Water Uptake Through Roots Architecturementioning
confidence: 99%
“…The spatial distribution of all root parts in a particular growth environment is referred to as root system architecture and defines the available zone of water and nutrients. This plays an important role in abiotic stress tolerance, crop performance and yield [29]. Root architecture is dynamic and affected by the external environment that impacts the way in which a plant detects and responds to its surroundings [30,31].…”
Section: Controlling Water Uptake Through Roots Architecturementioning
confidence: 99%
“…According to Akpan and Mbah (2016), the root system is the link between the soil nutrient and plant productivity. Paez-Garcia et al (2015) noted that different root traits enable plants to respond, adapt and thrive in different environments, which implies that root traits can be the focus of crop breeding effort. Watanabe et al (1997), Singh et al (1999) and Comas et al (2013) identified large root diameters, long roots and heavy root biomass and density as traits associated with the development of plant productivity in drought conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Functions like plant adaptation are played by different TFs which are capable of regulating several downstream genes essential for protection against drought [58,59]. TFs are potential candidate genes for developing drought tolerant plants and regulators of various genes that help the plants to effectively sustain drought stress.…”
Section: Genetic Engineering Of Crop Plants For Drought Tolerance: Romentioning
confidence: 99%